MANAJEMEN PEMERINTAHAN DALAM PEMUNGUTAN PAJAK SARANG BURUNG WALET OLEH BADAN PENDAPATAN DAERAH KABUPATEN INDRAGIRI HILIR TAHUN 2023 - Gemilang, Ananta Widya; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the suboptimal implementation of the potential swallow's nest tax collection on the Regional Original Revenue (PAD) of Indragiri Hilir Regency. Regional Original Revenue (PAD) is one of the regional government's financial resources in implementing regional autonomy. The relationship between government management in swallow's nest tax collection is the discrepancy between the set target and the actual revenue, indicating problems in governance or management, ranging from planning, organization, implementation, and supervision. The Regional Revenue Agency is a regional apparatus directly responsible for the tasks and functions supporting government affairs in the field of regional revenue management/management of regional taxes and levies. The purpose of this research is to determine how the Regional Revenue Agency of Indragiri Hilir Regency managed the swallow's nest tax collection in 2023. The research location is in Indragiri Hilir Regency, specifically at the Regional Revenue Agency office. This study uses Taliziduhu Ndraha's Government Management Theory, which encompasses four indicators: government planning, organization of government resources, utilization of government resources, and government oversight. The study found that the government management carried out by the Indragiri Hilir Regency Regional Revenue Agency in 2023 appears to be ineffective and inefficient. This may occur because the government management carried out has not met the indicators of government management, starting from government planning, organization and utilization of government resources, and government oversight, which has not been implemented. Consequently, it cannot achieve its government goals, namely the target realization of swallow's nest tax revenue in 2023. Keywords: Government Management, Collection, Tax